Comparison of Penetrating and Blunt Traumatic Diaphragmatic Injuries - Sang Su Lee; Sung Youl Hyun; Hyuk Jun Yang; Yong Su Lim; Jin Seong Cho; Jae Hyug Woo (Journal of Trauma and Injury)
Purpose Traumatic diaphragmatic injury (TDI) is no longer considered to be a rare condition in Korea. This study investigated differences in the prevalence of accompanying injuries and the prognosis in patients with traumatic diaphragmatic damage according to the mechanism of injury. Methods We retrospectively reviewed the medical records of patients with TDI who were seen at a regional emergency medical center from January 2000 to December 2018. Among severe trauma patients with traumatic diaphragmatic damage, adults older than 18 years of age with a known mechanism of injury were included in this study. Surgery performed within 6 hours after the injury was sustained was defined as emergency surgery. We assessed the survival rate and likelihood of respiratory compromise according to the mechanism of injury. Results In total, 103 patients were analyzed. The patients were categorized according to whether they had experienced a penetrating injury or a blunt injury. Thirty-five patients had sustained a penetrating injury, and traffic accidents were the most common cause of blunt injuries. The location of the injury did not show a statistically significant difference between these groups. Severity of TDI was more common in the blunt injury group than in the penetrating injury group, and was also more likely in patients with respiratory compromise. However, sex, the extent of damage, and the initial Glasgow coma scale score had no significant relationship with severity. Conclusions Based on the findings of this study, TDI should be recognized and managed proactively in patients with blunt injury and/or respiratory compromise. Early recognition and implementation of an appropriate management strategy would improve patients’ prognosis. Multi-center, prospective studies are needed in the future.